Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00125-014-3374-x
|View full text |Cite
|
Sign up to set email alerts
|

Statins and glycaemic control in individuals with diabetes: a systematic review and meta-analysis

Abstract: Statin treatment is associated with a modest increase in HbA1c in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 40 publications
6
70
2
5
Order By: Relevance
“…The recently growing fear for adverse effects of statins could have been a result of an FDA warning (published in 2012) on the increased risk of type 2 diabetes development in statin-treated patients [17]. Although clinical studies and meta-analyses conducted so far have confirmed the existence of this relationship, the effect of statin therapy on glucose homeostasis seems relatively minor -in non-diabetic patients treated with statins fasting glycemia is on average only 3 mg/dL higher than in subjects not receiving these drugs, and in diabetic patients statin use is associated with an increase in the proportion of glycated hemoglobin (HbA 1c ) by 0.12% compared to diabetics not treated with statins [18][19][20]. Although the results of a recently published METSIM study suggest that the risk of type 2 diabetes development on statin therapy might be higher than previously anticipated, still, the undeniable benefits of statin use in patients with high or very high total cardiovascular risk overweight the potential risk of their adverse effects [21].…”
Section: Discussionmentioning
confidence: 96%
“…The recently growing fear for adverse effects of statins could have been a result of an FDA warning (published in 2012) on the increased risk of type 2 diabetes development in statin-treated patients [17]. Although clinical studies and meta-analyses conducted so far have confirmed the existence of this relationship, the effect of statin therapy on glucose homeostasis seems relatively minor -in non-diabetic patients treated with statins fasting glycemia is on average only 3 mg/dL higher than in subjects not receiving these drugs, and in diabetic patients statin use is associated with an increase in the proportion of glycated hemoglobin (HbA 1c ) by 0.12% compared to diabetics not treated with statins [18][19][20]. Although the results of a recently published METSIM study suggest that the risk of type 2 diabetes development on statin therapy might be higher than previously anticipated, still, the undeniable benefits of statin use in patients with high or very high total cardiovascular risk overweight the potential risk of their adverse effects [21].…”
Section: Discussionmentioning
confidence: 96%
“…Statin therapy slightly increases the development of new diabetes, 45 and this is more marked with higher dose statins. 46 The metabolic side effects of statins in people with diabetes are a minor increase in HbA1c of 1.3 mmol/mol (0.12%), 47 but this is trivial compared with the overwhelming evidence of cardiovascular risk reduction. For primary prevention, most trials and meta-analyses have demonstrated a significant benefit of statin therapy in reducing cardiovascular events in those with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In pooled analyses of nine trials involving 9696 patients over a follow-up period of 3.6 years, mean HbA1c levels increased by 0.2 % in patients randomized to statin versus control treatment. 5 This dysglycemic effect of statins is apparently due to a reduction in both insulin sensitivity and secretion. 4 In addition, variants in the gene encoding HMG-CoA reductase, the target of statins, are associated with higher body weight, waist circumference, plasma glucose, and insulin concentrations, suggesting that the increased risk of type 2 diabetes due to statins may be partially explained by HMG-CoA reductase inhibition.…”
mentioning
confidence: 99%
“…7 A new dimension in this saga is suggested in this issue of JGIM by Mansi et al, who report that statin use may be associated with diabetic complications in a retrospective cohort study of adult patients enrolled in the US military's Tricare program in San Antonio, TX. 8 The authors selected patients without cardiovascular problems or significant comorbid conditions and, using propensity scores to match the two groups, selectedstatin treatment in patients with type 2 diabetes was shown to lead to a modest increase of 0.12 % in HbA1c levels compared to controls over a 3.6-year follow-up period, 5 although details were missing on the statin drugs and dosages as well as on whether antidiabetic treatment was more aggressive in statin users, two parameters that may have contributed to underestimation of the increase in HbA1c. However, this small change is unlikely to have a significant effect on the incidence or severity of diabetic complications (particularly cardiovascular events) in newly diagnosed diabetic patients.…”
mentioning
confidence: 99%